Penerapan Metode 5S Terhadap Lingkungan Kerja Pada Proses Pembuatan Tahu Di UD. Ari Berkah - Khoir, Muhammad Fikri; Sutrisno, Sutrisno (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2024)
UD. Ari Berkah is a home industry that operates in the field of making tofu. This tofu industry consists of several stages, namely soaking, washing, grinding, cooking, filtering, clotting, molding and cutting. This research aims to find out how long the process of making tofu takes before and after implementing the 5S method and wants to know an overview of the application of 5S in the work environment. In this research, researchers conducted direct interviews with owners and workers and made direct observations at the research site. The method in this research uses the 5S method. The stages of the 5S Method are designing improvements to the work environment, determining the time before and the proposed time for improvements after implementing 5S and the layout before and proposals after implementing 5S. The results in this study determined that UD. Ari Berkah has implemented 5S in the work environment, namely cleaning the work area, arranging equipment, cleaning soybean dregs waste, and providing 5S posters at work stations and working time before implementing the 5S method takes 13 hours 50 minutes. , whereas afterwards implementing the 5S method only takes 12 hours.